REQUIREMENTS FOR ETHICAL JUSTIFICATION OF CLINICAL TRIALS - Živojinović, Dragica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Conduction of the clinical trials on human subjects in order to gain data about efficiency and safety of the new drugs, medical devices and behavioral interventions is the essential part of the process of improvement in medical science. Yet, there are many potential risks of mistreat or abuse of the subject’s legal rights and safety once they are involved in these trials. Determinations of generally accepted demands of ethical justification for clinical trials provide decrease of risks for subjects that undergo the clinical trials. After analyzing the content of the international and regional declarations, ethical guidelines and local legal regulations, author finds that basic ethical requirements for conduction of the clinical trials are: scientific and social values and scientific validity, risk benefit ratio, fair subject selection, voluntary informed consent, respect of the subject’s personal rights and independent ethical comity review. In this work, author explains the purpose of these demands, determines their correlation and conclude that all of them stand in mutual connection and interrelation. Only cumulative fulfillment of all of the named requirements allows ethically acceptable approach to conduction of clinical trials with avoiding the exploitation and providing the fair and dissent environment for subjects with full respect to their legal rights and safety